Impact of Human Resource Accounting on the Financial Performance of Deposit Money Banks in Nigeria - Oyaide, Faith Afoke; Aminu, Ibrahim Yakasai; Lateef, Saheed Ademola (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study investigated the impact of human resource accounting on the financial performance of deposit money banks in Nigeria. Specifically, the study examined the impact of staff remuneration, staff training, and the cost of healthcare on the financial performance of Deposit Money banks in Nigeria. The study adopted the ex-post facto research design. Data were sourced from annual published accounts of Deposit Money Banks listed on the Nigerian Stock Exchange for the period 2018-2022. Descriptive statistics and correlation were used in the analysis of the data. Panel analysis was further used to test the hypotheses at the 5% level of significance. Findings from the investigation revealed that staff remuneration and the cost of health care and safety have no significant effects on EPS, while the cost of staff training has a significant effect on EPS of the sampled listed deposit money banks. The study, therefore, recommended the need for staff remuneration to be improved so that banks’ staff can put in their best to achieve better performance.